∫(e-e^x)dx
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 11:52:27
∫(e-e^x)dx∫(e-e^x)dx∫(e-e^x)dx∫(e-e^x)dx=ex-e^x+C其中C为常数不定积分是导数的逆运算,你应该会的呀∫(e-e^x)dx=∫edx-∫e^xdx=ex-e
∫(e-e^x)dx
∫(e-e^x)dx
∫(e-e^x)dx
∫(e-e^x)dx =ex-e^x+C其中C为常数
不定积分是导数的逆运算,你应该会的呀
∫(e-e^x)dx=∫edx-∫e^xdx=ex-e^x+C
∫(e-e^x)dx
=ex-e^x+c
∫(e-e^x)dx
积分∫dx /(e^x+e^-x)
∫1/(e^x+e^(-x))dx,
∫ e^x / x dx
求不定积分: ∫dx/(e^x-e^(-x))dx
∫[dx/(e^x(1+e^2x)]dx
∫ e^x-e^(-x)dx=e^x+e^(-x)|=e+1/e-2
∫e^(-x) cosx dx
∫ e^(x^2)dx
∫dx/√e^x
求不定积分,∫e^X(3^X-e^X)dx
∫X^2 e^-X^3 dx.
求不定积分 ∫x(e^x) dx
求积分∫ e^(x*x)dx
∫(x+e的x次方)dx
∫【x(cosx+e^2x)dx】
积分 ∫(e^x)/(x+2)dx
∫(x sinx)e^x dx